Provenance of Neoproterozoic to upper Cretaceous sedimentary rocks, eastern Greenland: Implications for recognizing the sources of sediments in the Norwegian Sea - Sláma, J. (Jiří); Walderhaug, O.; Fonneland, H.; Kosler, J.; Pederson, R. B. (Sedimentary Geology, 2011)
Detrital zircon U–Pb and Lu–Hf isotope data from Neoproterozoic to Cretaceous sandstones exposed in eastern Greenland, 70°30′–74°N, are reported to characterize and evaluate the provenance from Greenland during pre-breakup and post-breakup sedimentation in the Norwegian–Greenland Sea. Middle Devonian to Lower Cretaceous samples all show similar detrital zircon age distributions characterized by variable Archean populations, abundant Proterozoic populations ranging from ca. 2000 to 900 Ma and a Caledonian population peaking at ca. 440 Ma. Neoproterozoic sediments of the Eleonore Bay Supergroup give a more narrow age distribution with a dominant age peak at 1100 to 1000 Ma, a secondary peak at 1700–1400 Ma, and rare Archean to Paleoproterozoic ages. The scarcity of Archean zircons could indicate a rather limited role of the Archean basement rocks of the eastern Greenland Caledonian orogenic belt as a source for some of the analyzed younger sedimentary rocks.